Pengaruh Kualitas Pelayanan dan Word of Mouth Terhadap Loyalitas Pasien Klinik Biddokkes Polda Lampung - Ari Widia; Iskandar Ali Alam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Healthcare services are a crucial sector that requires effective strategic and operational management to meet public needs. Klinik Biddokkes Polda Lampung faces challenges in maintaining patient loyalty, as reflected in the retention rate of only 57% of total patients in 2025. This phenomenon indicates a gap between patients’ expectations of service quality and the actual experience received, as well as the lack of positive word of mouth. This study aims to analyze the effect of service quality and word of mouth on patient loyalty at Klinik Biddokkes Polda Lampung. A quantitative research method was employed using multiple linear regression analysis. The population consisted of clinic patients, with samples selected through purposive sampling. Data were collected through patient satisfaction surveys, internal quality audits, and structured questionnaires, then analyzed using validity and reliability tests, t-test, F-test, and coefficient of determination (R²). The results show that service quality significantly affects patient loyalty with a significance value of 0.028, while word of mouth has a stronger influence with a significance value of 0.000. The F-test indicates that both variables simultaneously have a significant effect on patient loyalty, with an F-value of 38.506 and a significance of 0.000. The R² value of 0.443 demonstrates that 44.3% of the variation in patient loyalty can be explained by service quality and word of mouth, while the remaining 55.7% is influenced by other factors outside the research model. In conclusion, patient loyalty at Klinik Biddokkes Polda Lampung is influenced by both service quality and word of mouth, with word of mouth being the dominant factor. Therefore, strategies to enhance patient loyalty should be integrated by improving consistent service quality and strengthening communication and positive patient experiences to generate sustainable recommendations.